Oncologic and reproductive outcome after fertility-saving surgery in ovarian cancer - Ayhan, A.; Celik, H.; Taskiran, C.; Bozdag, G.; Aksu, T. (My University, 2003)
The rate of ovarian tumour diagnosis in reproductive age woman has increased parallel to the improvements in diagnostic methods and regular gynaecological visits. Because of this organ saving surgical procedures for the preservation of reproductive and endocrine functions have gained more interest. Conservative surgical approaches for ovarian tumours after surgical staging include cystectomy, unilateral salpingo-oophorectomy and unilateral salpingo-oophorectomy plus contralateral cystectomy. Ovarian tumours diagnosed in young ages tend to be low-stage low-grade malignancies. This not only enables but also necessitates preserving the fertility of women who have not completed their family. In invasive ovarian cancer, fertility saving surgery is confined to early-stage and low-grade disease. But, it also had been reported in advanced stages (up to Stage IIIc). Candidates for those procedures were selected according to the FIGO stage, grade, ploidy state, histological subtypes and patients' desire. Adjuvant chemotherapy is necessary for high-risk patients. The rate of recurrence following conservative and radical surgical procedures in low-stage and low-grade tumours are 9% and 11.6%, respectively; and disease-free and overall survival rates do not differ significantly. Prognosis of borderline ovarian tumours is excellent. Five and 20-year survival rates are 95% and 80%, respectively. Management of borderline tumours has evolved significantly in the last few decades. In contrast to invasive ovarian cancer, borderline tumours can be operated on conservatively at all stages. Chemotherapy is rarely prescribed even in advanced stages. Eighty percent of malignant germ cell tumours are diagnosed less than 30 years of age, and 70-75% of patients have Stage I disease. Conservative surgery is generally used in malignant germ cell tumours even in advanced stages. The relation between ovulation induction and tumour recurrence is not consistent in the literature. Spontaneous pregnancy rates following fertility saving surgery has been reported as 60-88%. Because of this over-treatment of these patients for fertility should be avoided. Briefly, fertility saving surgery can be performed safely in germ cell, borderline and early stage epithelial ovarian tumours in selected cases. Any increment in the rate of tumour recurrence following ovulation induction has not yet been demonstrated. Menstrual irregularities caused by chemotherapy are transient. The congenital malformation rate of ovarian cancer patients is slightly higher than that of the normal population, but no significant difference has been observed between patients who received or did not receive chemotherapy.
Keywords: Fertility outcome; Fertility saving surgery; Oncologic outcome; Ovarian cancer